2018
DOI: 10.1007/s11255-018-1913-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of periodontal disease treatment in patients with continuous ambulatory peritoneal dialysis

Abstract: Periodontal disease is an important source of inflammation in diabetic CAPD patients and treatment of periodontal disease can be monitored by inflammatory markers including TNF-alpha, PTX-3, IL-6, and Hs-CRP. TNF-alpha may be useful and more sensitive monitoring inflammation in healthy patients and diabetic patients after periodontal treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 36 publications
3
31
0
Order By: Relevance
“…Pradeep et al, () suggested that PTX‐3 is a good indicator of periodontal tissue destruction, and its association with periodontal clinical parameters has been shown. There were very few studies that investigate the changes of PTX‐3 level after periodontal therapy (Rauten et al, ; Tasdemir et al, ; Taşdemir, Taşdemir et al, ; Varghese Mathew & Sheeja Varghese, ). Our result was in accordance with the study of Mathew et al(Varghese Mathew & Sheeja Varghese, ) but contrast with our previous study (Taşdemir, Taşdemir et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pradeep et al, () suggested that PTX‐3 is a good indicator of periodontal tissue destruction, and its association with periodontal clinical parameters has been shown. There were very few studies that investigate the changes of PTX‐3 level after periodontal therapy (Rauten et al, ; Tasdemir et al, ; Taşdemir, Taşdemir et al, ; Varghese Mathew & Sheeja Varghese, ). Our result was in accordance with the study of Mathew et al(Varghese Mathew & Sheeja Varghese, ) but contrast with our previous study (Taşdemir, Taşdemir et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Many inflammatory markers are associated with periodontal disease (Fujita, Ito, Sekino, & Numabe, ; Tasdemir et al, ; Taşdemir, Taşdemir, Koçyiğit, & Gürgan, ). C‐reactive protein is an acute‐phase protein, and elevated levels of high sensitivity C‐reactive protein (Hs‐CRP) are related to disease severity (Bansal, Pandey, Deepa, & Asthana, ).…”
Section: Introductionmentioning
confidence: 99%
“…Hyperglycemia adversely affects all soft and hard tissues of the periodontium [10]. So compared to their normoglycemic counterparts, people with diabetes mellitus, especially poorly controlled, have more gingivitis, both children/adolescents [11][12][13][14][15] and adults [10,16], especially seniors ages 65 years and older [17]; greater prevalence and severity [2,3,10,18,19] as well as progression [20] of periodontitis; and have lost many more teeth, the ultimate result of unmanaged periodontitis [21,22]. Panel 1A in Fig.…”
Section: Periodontal Diseasesmentioning
confidence: 99%
“…Periodontitis is also associated with diabetic nephropathy [20,63]. A study among 207 patients with type 2 diabetes in India reported periodontitis to be associated with glycemic control and diabetic nephropathy [63].…”
Section: Diabetic Nephropathymentioning
confidence: 99%
See 1 more Smart Citation